New challenges for human resource management in academic institutions: A qualitative survey of emerging demands in Czech higher education - Urban, Jan; Caha, Zdeněk; Procházková, Michaela (Edelweiss Applied Science and Technology, 2024)
The effectiveness of academic institutions in achieving educational excellence, advancing research, and addressing societal issues is significantly influenced by the management of their human capital. This includes the qualifications, skills, and development opportunities for both academic and non-academic staff, as well as the systems in place for performance management and career advancement. Unlike corporate HR managers, those in universities often have limited authority over cross-functional areas such as career planning, organizational culture, and performance management. This paper investigates the main challenges and risks that arise from the typically underdeveloped HR management systems within universities. Through a qualitative analysis based on semi-structured interviews with HR managers from Czech universities, the study evaluates their awareness of these challenges and examines the strategies they are considering to address them.